Understanding the Role of Researchers in Engaging and Communicating Sciences with Inuit Youth - Gbetholancy, Claudia (University of Guelph, 2022)
Over the past decade, Inuit and non-Inuit researchers have worked in partnerships to conduct research that give voice to non-Western knowledge systems. However, studies show that although many researchers demonstrate a keen interest in engaging with Inuit youth, they often lack the resources and communication skills to do so. This study aims to assess the perspectives of experts on the role of researchers in engaging and communicating sciences with Inuit youth. This study was conducted using semi-structured interviews and a modified Delphi method to explore the perspectives of experts, including researchers, educators, members of Inuit organizations, public servants, and communication specialists. Findings show that the role of researchers in engaging and communicating sciences with Inuit youth is to build relationships based on trust, to work in the spirit of co-creation, to create opportunities for research capacity building, and to develop resources to support meaningful youth engagement in Arctic research.